Sustainable Practices and Sustainable Resource Efficiency: Case of Subang’s MSMEs - Widarwati, Estu; Nurmalasari, Nunik; Zorafiyan, Devran Firmansyah; Rahmah, Nur Fika Aulia (STIESA Press, 2026)
This research emphasizes the importance of implementing sustainable practices in Micro, Small, and Medium Enterprises (MSMEs) in optimizing sustainable resource efficiency. This study aims to find out the extent of sustainable practices on resource efficiency in MSMEs in Subang Regency, especially Subang District by 2025. The methodology of this study uses a quantitative method with verifiable descriptive statistical analysis, data was collected through questionnaires, literature studies, and observations with a sample of 40 respondents. The data obtained were analyzed using classical assumption tests, simple linear regression, and hypothesis tests using the SPSS 2025 analysis tool. The results showed that the implementation of sustainable practices had a significant influence on resource efficiency, with a contribution of 34.4%. Sustainable practices in MSMEs in Subang Regency, especially Subang District, have important implications that can improve the efficiency of resource use. This research can encourage MSMEs actors to be more aware of the importance of implementing sustainable practices.